Validity of a repeated-sprint ability test in young soccer players - Barbero-Alvarez, J. C.; Pedro, R.E.; Nakamura, F. Y. (Science & Sports, 2013)
Objective: This study examined the direct validity of a repeated-sprint ability test (RSAT) in predicting match high-intensity running in young soccer players (n = 15, 14 years). Methods: Players` RSAT performance (7 × 30 m with < 24 s passive recovery) was assessed 24 h before a competitive match and performance compared with high-intensity activity during a match. Match performance was tracked with GPS technology and heart rate (HR) recorded with short-range telemetry. Results: During the first half, players covered 3526 ± 527 m of which 14.9 ± 4.5% was performed at speed faster than 13 km/h (HIA). The RSA variables were significantly correlated with HIA, match HR and peak speed (r from 0.59 to 0.82, P < 0.05). Conclusion: This study's findings showed that RSAT was significantly related to match physical and physiological demands in youth soccer. These results support the direct validity of RSAT in predicting match high-intensity running in young soccer players.